Diagnosis of Vibrio cholerae isolated from patients with Vibriosis in Thi-Qar province - helal, Kareema; Al-Mozan, Hanaa (University of Thi-Qar Journal of Science, 2024)
The gram-negative bacteria Vibrio cholerae is the source of cholera a severe case of diarrhea. Cholera occurs either sporadically, epidemically, or endemic. Overpopulation, untreated water supplies, and unsanitary circumstances have historically been closely linked to cholera outbreaks and pandemics. This study aimed to determine the accuracy of routine and advanced biochemical methods in diagnosing Vibrio cholerae, the extent of the prevalence of bacteria and which age groups and gender are most susceptible to infection. Stool specimens were obtained from patients suspected with cholera disease from both gender in different hospitals in Thi-Qar province through the period from September to December 2023. Cary Blair medium was used to transfer the suspicious stool specimens to the Thi-Qar province's Central Health Laboratory. Routine and advanced biochemical methods were used to diagnose Vibrio cholerae. A total of 400 specimens of stool from patients suspected cholera have been collected, only (45) isolates were given growth V. cholerae with 11.25 % in biochemical routine test while in API20 E test 41 isolates were given growth V. cholerae with 10.25%. The age group with the highest infection rate was 55–65, whereas the age group with the lowest infection rate was under 5 years. With no statistically significant difference, the illness most commonly impacted females. The results have showed different morphology characteristics of all V. cholerae isolates which grow on different media. Routine and advanced biochemical tests may not give the same results, which have prompted to search for a more accurate and faster method of diagnosis.